Methods of Modification and Semantics of Foreign Anthroponyms in Russian Internet Discourse (Example of Nomination of Members of British Royal Family) - Y. A. Tregubova; E. V. Lavrishcheva (Научный диалог)
The results of a study of the functioning peculiarities of modified foreign anthroponyms in the Russian-language Internet discourse is presented in the article. The main methods of word formation, the structure and semantics of foreign occasional anthroponyms in the Russian-language Internet discourse are considered. The relevance and novelty of the study is due to the choice of linguistic material, which were foreign-language anthroponyms in Russian, in particular, modified names of members of the British royal family. It is shown that these occasional nominations embody the emotional and evaluative attitude of Russian-speaking Internet users to members of the royal family. The results of a structural and comparative analysis of modified foreign anthroponyms used by Russian-speaking Internet users are presented. An attempt is made to show how the derivational means of the Russian language can reflect the subjective connotation of occasional derivatives. The main word-formation models in the field of occasional anthroponymy of the Russian language are revealed. It is concluded that the most productive way of modifying foreign anthroponyms in the Russian-language Internet discourse is suffixation. The semantics of the identified word-formation models is analyzed, their emotional-expressive function in the language is studied. The results of a statistical analysis of the use of the main methods of creating modified foreign anthroponyms in the Russian-language Internet discourse are presented.